Generation of controllable gaseous H2S concentrations using microfluidics. Issue 8 (23rd January 2018) - Christoforidis, Theodore; Driver, Tom G.; Rehman, Jalees; Eddington, David T.
Abstract : Hydrogen sulfide (H2 S) plays an important role as an intracellular signaling molecule, but is difficult to control in vitro . This paper presents a simple way to generate stable H2 S conditions via microfluidic networks. Abstract : Hydrogen sulfide (H2 S) plays an important role as an intercellular and intracellular signaling molecule, yet its targets are not well understood. As a molecule it easily evaporates and it is hard to acquire stable concentration for in vitro studies, constituting a major problem for the field to identify its downstream targets and function. Here we develop a microfluidic system that can provide consistent and controllable H2 S levels in contrast to the current method of delivering large bolus doses to cells. The system relies on the permeability of H2 S gas through a polydimethylsiloxane thin membrane. A hydrogen sulfide donor, sodium hydrosulfide, is perfused in the microchannels below the gas permeable membrane and gaseous H2 S diffuses across the membrane, providing a stable concentration for up to 5 hours. Using electrochemical sensors within 3 ppm range, we found that H2 S concentration was dependent on two parameters, the concentration of H2 S donor, sodium hydrosulfide and the flow rate of the solution in the microchannels. Additionally, different H2 S concentration profiles can be obtained by alternating the flow rate, providing an easy means to control the H2 S concentration. Our approach constitutes a unique method for H2 S delivery for in vitro and ex vivo studies and is ideally suited to identify novel biological processes and cellular mechanisms regulated by H2 S.